2009
DOI: 10.1159/000231632
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Improvement in Tinnitus after Modified Tinnitus Retraining Therapy Enhanced by a Variety of Psychological Approaches

Abstract: This work evaluates an enhanced tinnitus retraining therapy (TRT) for patients with chronic tinnitus based on different group therapeutic interventions in a day hospital setting. Therapy for chronic tinnitus is intended to improve the way patients cope with tinnitus by learning how to reduce tinnitus-induced impairments. Short-term and long-term changes in stress variables and tinnitus-related distress were investigated using 3 psychometric instruments. Patients received 7 consecutive days of a multidisciplina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 71 publications
1
51
0
7
Order By: Relevance
“…In our recent study, we showed that tinnitus therapy was most effective in the patients with higher perceived stress [Seydel et al, 2010]. In order to examine the outcome of therapy in the implanted patients with different degrees of tinnitus-related distress or perceived stress, the TQ and PSQ scores were divided into 2 subgroups with low and high levels each.…”
Section: Effect Of the Severity Level Of Tinnitus And Perceived Stresmentioning
confidence: 99%
“…In our recent study, we showed that tinnitus therapy was most effective in the patients with higher perceived stress [Seydel et al, 2010]. In order to examine the outcome of therapy in the implanted patients with different degrees of tinnitus-related distress or perceived stress, the TQ and PSQ scores were divided into 2 subgroups with low and high levels each.…”
Section: Effect Of the Severity Level Of Tinnitus And Perceived Stresmentioning
confidence: 99%
“…Davies et al (17) found that relaxation exercises significantly lowered annoyance ratings at one month follow-up despite having no significant changes in the loudness of tinnitus. In a recent study muscle relaxation therapies were found to significantly reduce both short and long-term tinnitus related distress (18). When the TRQ and THQ scores of patients that carried out only relaxation exercises were interpreted, no statistically significant difference was found among them.…”
Section: Discussionmentioning
confidence: 93%
“…However, CBT studies showed large effects size. As the 8 studies in the present review involved combined approaches 22,28,31,33,35,36,38,40 therefore, making it difficult to extract the role of individual intervention approach.…”
Section: Discussionmentioning
confidence: 99%
“…Seydel et al 35 evaluated an enhanced TRT for 237 patients suffering from chronic tinnitus. Short term and long term changes in stress variable and tinnitus related distress was investigated using TQ, TSQ and ADS.…”
Section: Ariizumi Et Almentioning
confidence: 99%